Argumentasi Kemutawatiran Qira’at Sab‘ah - Nawawi, Fuad (SUHUF, 2024)
Some scholars argue that the qira’at sab‘ah have a single (ahad) transmission chain because their transmission is from one individual to another, resulting in a limited number of transmitters. Others believe that the qira’at sab‘ah have a mutawatir (many) transmission chains because their transmission is from one community to another, thus involving a more significant number of transmitters. Both polarizations lack a solid theoretical basis. In this article, the author analyzes the Qur’anic qira’at, which originated from oral traditions, using Walter Ong’s theory of orality as presented in his book Orality and Literacy. Through a qualitative method, the author collects and analyzes written words from various references by reducing and presenting the data and concluding. This study argues that the mutawatir status of the qira’at sab‘ah is logical and plausible. The argument is that a word does not exist in oral tradition because it is formed by letters or their arrangement. Instead, a word and its meaning emerge through the convention between speakers and listeners, resulting from the socio-cultural negotiation of a particular community. Such a convention and tradition presupposes the existence of a community that sustains the knowledge (i.e., the Qur’an) based on this oral tradition.